2019
DOI: 10.1039/c8dt05052j
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative activation of O–H and S–H bonds across the Co–P bond of an N-heterocyclic phosphido complex

Abstract: A cobalt N-heterocyclic phosphido complex is shown to cleave element–hydrogen bonds via a metal–phosphorus ligand cooperative pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…[23] In contrast, the reaction between (PPP)Co(PMe 3 ) and thiophenol was found to be much more complex, featuring an intermolecular ligand exchange process, where the (PP H P)Co(SPh)(PMe 3 ) complex was initially formed, but ultimately converted into the more thermodynamically stable (PP SPh P)Co(H)(PMe 3 ) product in solution. [24] Both the kinetic and thermodynamic product in the cobalt case remained five-coordinate with no evidence for dissociation of the PMe 3 ligand. Although 4 could not be broken into two monomeric species either through the addition of an exogenous ligand or via reaction with thiophenol, we were hopeful that 5 would be a reactive complex due to its differing structure, such that no large reorganization of the binding in the phosphine side arms would be required for it to form two monomeric complexes.…”
Section: Reactivity Studies Of 3 Andmentioning
confidence: 92%
See 3 more Smart Citations
“…[23] In contrast, the reaction between (PPP)Co(PMe 3 ) and thiophenol was found to be much more complex, featuring an intermolecular ligand exchange process, where the (PP H P)Co(SPh)(PMe 3 ) complex was initially formed, but ultimately converted into the more thermodynamically stable (PP SPh P)Co(H)(PMe 3 ) product in solution. [24] Both the kinetic and thermodynamic product in the cobalt case remained five-coordinate with no evidence for dissociation of the PMe 3 ligand. Although 4 could not be broken into two monomeric species either through the addition of an exogenous ligand or via reaction with thiophenol, we were hopeful that 5 would be a reactive complex due to its differing structure, such that no large reorganization of the binding in the phosphine side arms would be required for it to form two monomeric complexes.…”
Section: Reactivity Studies Of 3 Andmentioning
confidence: 92%
“…[23] In contrast, the reaction between (PPP)Co(PMe3) and thiophenol was found to be much more complex, featuring an intermolecular ligand exchange process, where the (PP H P)Co(SPh)(PMe3) complex was initially formed, but ultimately converted to the more thermodynamically stable (PP SPh P)Co(H)(PMe3) product in solution. [24] Both the kinetic and thermodynamic product in the cobalt case remained fivecoordinate with no evidence for dissociation of the PMe3 ligand.…”
Section: Reactivity Studies Of 3 Andmentioning
confidence: 93%
See 2 more Smart Citations
“…Many of the most successful cobalt hydroboration catalysts take advantage of the stability and rigidity imparted by tridentate pincer ligands. , We turn our attention herein to a (PPP) − pincer ligand that incorporates an N-heterocyclic phosphido (NHP – ) moiety in the central donor position flanked by two diarylphosphine side arms . We have previously demonstrated that the tridentate (PPP) − pincer ligand can engage in metal–ligand cooperativity, through either bifunctional substrate activation across the metal-P bond or ligand-assisted redox processes. …”
Section: Introductionmentioning
confidence: 99%